Cathode active material, preparation method thereof, secondary battery and device
By using the secondary particles of the hollow radiation structure as a positive active material, the problem of poor circulation stability under fast charge conditions under the conditions of fast charge is solved, and higher structural stability and magnification performance are achieved, and the cycle life of the battery is extended.
Patent Information
- Application Number
- CN202411361411.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-01-28
Smart Images

Figure CN119381444A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of energy storage, and in particular to a positive electrode active material and a preparation method thereof, a secondary battery and a device. Background Art
[0002] In recent years, electric vehicles have gradually gained popularity. However, compared with traditional fuel vehicles, long charging time and rapid reduction in battery life have become the main problems hindering the development of electric vehicles. Therefore, improving fast charging capabilities and battery life has become a common development goal for battery manufacturers and vehicle manufacturers. The performance of electrode materials under high-rate conditions can greatly affect the fast charging capability of the battery, and its structural stability under charge and discharge cycles can greatly affect the life of the battery. In view of this, the long-term cycle stability of electrode materials under fast charging conditions needs to be solved urgently. The ternary material nickel cobalt manganese oxide (NCM) is a positive electrode material with a high use capacity and is one of the most commonly used positive electrode materials for power batteries. However, it has defects such as poor kinetics, phase change, and microcracks, which leads to rapid capacity decay under fast charging conditions, affecting the battery life of the power battery.
[0003] Therefore, current positive electrode active materials and preparation methods thereof, secondary batteries and devices still need to be improved. Summary of the invention
[0004] The inventors found that in order to achieve the cycle stability of the power battery under fast charging conditions, on the one hand, it is necessary to improve the lithium ion transmission kinetics of the positive electrode material, and on the other hand, it is necessary to reduce the microcracks and interface side reactions caused by phase change under high SOC (State of Charge, battery state of charge). In view of this, the present application provides a positive electrode active material and its preparation method, secondary battery and device. The secondary particles in the positive electrode active material provided by the present application have a hollow radial (radiating) structure, which can well release the stress generated by the phase change of the ternary positive electrode material under high SOC, reduce the microcracks generated by the stress, and avoid the exposed fresh interface from reacting with the electrolyte, thereby achieving the improvement of the cycle stability of the material; and the secondary particles have a radial structure, the aspect ratio of the primary particles is larger, more lithium ion transmission channels can be exposed, and good electrolyte wettability can be achieved. The crystal orientation degree (crystal orientation ratio) of the grains in the secondary particles is high, and the contact between the grains with close orientations is conducive to the rapid transmission of lithium ions, improving the material rate performance and charge and discharge capacity, thereby meeting the requirements of high energy density and fast charge and discharge, improving the cycle stability of the material under fast charging conditions and extending the cycle life of the material.
[0005] One aspect of the present application provides a positive electrode active material, the chemical formula of which is Li x Ni y Coz M1 a M2 b O c A d , 0.95≤x≤1.05, 0≤y≤1, 0≤z≤1, 0≤a≤1, 0≤b≤0.1, y+z+a+b=1, 1≤c≤2, 0≤d≤2, c+d≤2, M1 includes at least one of Mn and Al, M2 includes at least one of Zr, Zn, Cu, Cr, Sr, Mo, Mg, Fe, Ta, V, Ti, Y, La and Nb, and A includes at least one of N, F, S and Cl; the positive electrode active material includes: secondary particles, the secondary particles are formed by aggregation of primary particles, the secondary particles have a hollow portion inside, the long axis direction of the primary particles in the secondary particles is toward the hollow portion, and the particles are arranged in an emitting manner; wherein the orientation distribution of the grains is tested by backscattered electron diffraction, the collection surface is a cross section through the center of the secondary particles, the normal direction of the collection surface is the Z-axis direction, and the secondary particles parallel to the Z-axis direction <001> The crystal orientation ratio of the crystal orientation is N, which satisfies: 15%≤N≤60%.
[0006] Another aspect of the present application provides a method for preparing a positive electrode active material, which includes: mixing metal oxide particles with an alkaline solution to form a first mixed solution; adding a metal salt mixed solution, a precipitant and a complexing agent to the first mixed solution, and sequentially performing a heating reaction treatment and an aging treatment to form a ternary precursor having a hollow structure inside; wherein the metal salt mixed solution includes Ni, Co and Mn elements; mixing the ternary precursor and a dopant, and performing a first calcination treatment to form a first product; mixing the first product and a first coating agent, and performing a second calcination treatment to form a second product; mixing the second product and a second coating agent, and performing a third calcination treatment to form the positive electrode active material; wherein the positive electrode active material includes: secondary particles, the secondary particles are formed by aggregation of primary particles, the secondary particles have a hollow portion inside, the major axis direction of the primary particles in the secondary particles is toward the hollow portion, and they are arranged in a radial shape.
[0007] Another aspect of the present application provides a secondary battery, which includes the positive electrode active material described above or the positive electrode active material formed by the preparation method described above.
[0008] Another aspect of the present application provides a device, which includes the secondary battery described above.
[0009] The beneficial effects of this application are:
[0010] The positive electrode active material of the present application includes: secondary particles formed by the aggregation of primary particles, the interior of the secondary particles has a hollow part, the long axis direction of the primary particles in the secondary particles is toward the hollow part, and is arranged in an radiating shape. On the one hand, the secondary particles have a hollow radial (radiating) structure, which can well release the stress (intergranular stress) generated by the phase change of the ternary positive electrode material under high SOC, improve the structural stability of the material, have good mechanical properties, reduce the microcracks caused by stress, avoid the exposed fresh interface from reacting with the electrolyte, thereby achieving the improvement of the cycle stability of the material. On the other hand, the radial structure of the secondary particles, the aspect ratio of the primary particles is larger, more lithium ion transmission channels can be exposed, and good electrolyte wettability can be achieved. The crystal orientation degree (crystal orientation ratio) is high, and the contact between the grains with close orientation is conducive to the rapid transmission of lithium ions, improving the material rate performance and charge and discharge capacity, thereby meeting the requirements of high energy density and fast charge and discharge, improving the cycle stability of the material under fast charge conditions, and extending the cycle life of the material. In addition, the long axis direction of the primary particles in the secondary particles is toward the hollow part and arranged in a radial shape. The secondary particles arranged in the radial direction have high ion conductivity and excellent electrical conductivity, which further reduces the lithium ion diffusion impedance inside the material. Therefore, based on the above improvements, the positive electrode active material of the present application has at least one of the following advantages: excellent material structure stability, fast charging performance, rate performance, cycle stability performance and calendar life. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 is a schematic diagram of the cross-sectional structure of secondary particles in a positive electrode active material according to an embodiment of the present application;
[0012] Figure 2 It is a scanning electron microscope image of secondary particles in a positive electrode active material according to one embodiment of the present application.
[0013] Figure 3 1 is a cross-sectional scanning electron microscope image of secondary particles in a positive electrode active material according to one embodiment of the present application.
[0014] Figure 4 It is a crystal plane distribution diagram of a backscattered electron diffraction test of secondary particles in a positive electrode active material according to one embodiment of the present application.
[0015] Figure 5 1 is a distribution diagram of the aspect ratio of primary particles in secondary particles of a positive electrode active material according to one embodiment of the present application. DETAILED DESCRIPTION
[0016] For simplicity, this application only specifically discloses some numerical ranges. However, any lower limit can be combined with any upper limit to form an undefined range; and any lower limit can be combined with other lower limits to form an undefined range, and any upper limit can be combined with any other upper limit to form an undefined range. In addition, each separately disclosed point or single value can itself be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an undefined range.
[0017] Unless otherwise specified, the terms used in this application have the commonly known meanings generally understood by those skilled in the art. Unless otherwise specified, the numerical values of the various parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the examples of this application).
[0018] A list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single component or multiple components. Item B may contain a single component or multiple components. Item C may contain a single component or multiple components.
[0019] The present application is further described below in conjunction with specific implementations. It should be understood that these specific implementations are only used to illustrate the present application and are not used to limit the scope of the present application.
[0020] 1. Positive electrode active materials
[0021] The first aspect of the present application provides a positive electrode active material, wherein the chemical formula of the positive electrode active material is Li x Ni y Co z M1 a M2 b O c A d, 0.95≤x≤1.05, 0≤y≤1, 0≤z≤1, 0≤a≤1, 0≤b≤0.1, y+z+a+b=1, 1≤c≤2, 0≤d≤2, c+d≤2, M1 includes at least one of Mn and Al, M2 includes at least one of Zr, Zn, Cu, Cr, Sr, Mo, Mg, Fe, Ta, V, Ti, Y, La and Nb, and A includes at least one of N, F, S and Cl; the positive electrode active material includes: secondary particles, the secondary particles are formed by aggregation of primary particles, the secondary particles have a hollow portion inside, the long axis direction of the primary particles in the secondary particles is toward the hollow portion, and the particles are arranged in an emitting manner; wherein the orientation distribution of the grains is tested by backscattered electron diffraction, the collection surface is a cross section through the center of the secondary particles, the normal direction of the collection surface is the Z-axis direction, and the secondary particles parallel to the Z-axis direction <001> The crystal orientation ratio of the crystal orientation is N, which satisfies: 15%≤N≤60%.
[0022] Thus, the positive active material of the present application includes: secondary particles formed by the aggregation of primary particles, the interior of the secondary particles has a hollow part, the long axis direction of the primary particles in the secondary particles is toward the hollow part, and they are arranged in an radiating shape. On the one hand, the secondary particles have a hollow radial (radiating) structure, which can well release the stress (intergranular stress) generated by the phase change of the ternary positive electrode material under high SOC, improve the structural stability of the material, have good mechanical properties, reduce the microcracks caused by stress, avoid the exposed fresh interface from reacting with the electrolyte, thereby achieving the improvement of the cycle stability of the material. On the other hand, the radial structure of the secondary particles, the aspect ratio of the primary particles is larger, more lithium ion transmission channels can be exposed, and good electrolyte wettability can be achieved. The crystal orientation degree (crystal orientation ratio) is high, and the contact between the grains with close orientation is conducive to the rapid transmission of lithium ions, improving the material rate performance and charge and discharge capacity, thereby meeting the requirements of high energy density and fast charge and discharge, improving the cycle stability of the material under fast charge conditions, and extending the cycle life of the material. In addition, the long axis direction of the primary particles in the secondary particles is toward the hollow part and arranged in a radial shape. The secondary particles arranged in the radial direction have high ion conductivity and excellent electrical conductivity, which further reduces the lithium ion diffusion impedance inside the material. Therefore, based on the above improvements, the positive electrode active material of the present application has at least one of the following advantages: excellent material structure stability, fast charging performance, rate performance, cycle stability performance and calendar life.
[0023] In some embodiments, the chemical formula of the positive electrode active material is Li x Ni y Co z M1 a M2 b O c A d, 0.95≤x≤1.05, 0≤y≤1, 0≤z≤1, 0≤a≤1, 0≤b≤0.1, y+z+a+b=1, 1≤c≤2, 0≤d≤2, c+d≤2, M1 includes at least one of Mn and Al, M2 includes at least one of Zr, Zn, Cu, Cr, Sr, Mo, Mg, Fe, Ta, V, Ti, Y, La and Nb, and A includes at least one of N, F, S and Cl. In some embodiments, x is 0.95, 0.97, 0.99, 1, 1.05 or any value therebetween. In some embodiments, y is 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 0.95, 0.96 or any value therebetween. In some embodiments, 0.6≤y≤0.75. In some embodiments, 0.8≤y≤0.96. In some embodiments, z is 0, 0.1, 0.15, 0.2, 0.25, 0.3, 0.4 or any value therebetween. In some embodiments, a is 0, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4 or any value therebetween, b is 0, 0.005, 0.01, 0.02, 0.05, 0.08, 0.1 or any value therebetween, c is 1, 1.5, 1.6, 1.7, 1.8, 1.9, 2 or any value therebetween. In some embodiments, d is 0, 1, 1.5, 1.6, 1.7, 1.8, 1.9, 2 or any value therebetween. In some embodiments, d is 0.
[0024] In some embodiments, the positive electrode active material includes: secondary particles, the secondary particles are formed by the aggregation of primary particles, the interior of the secondary particles has a hollow portion, the major axis direction of the primary particles in the secondary particles is toward the hollow portion, and they are arranged in a radial manner. In some embodiments, the secondary particles are spherical or quasi-spherical. It should be noted that a quasi-spherical body refers to an irregular sphere or a sphere-like polyhedron. In some embodiments, at least a portion of the primary particles in the secondary particles are arranged radially along the radial direction from the center of the secondary particles toward the surface. As a result, the secondary particles have a hollow radial (radiating) structure, which can well release the stress (intergranular stress) generated by the phase change of the ternary positive electrode material under high SOC, improve the structural stability of the material, have good mechanical properties, reduce microcracks caused by stress, and avoid the exposed fresh interface from reacting with the electrolyte, thereby achieving an improvement in the cyclic stability of the material. In addition, the major axis direction of the primary particles in the secondary particles is toward the hollow portion, and they are arranged in a radial manner. The secondary particles arranged in the radial direction have high conductivity and excellent electrical conductivity, which further reduces the lithium ion diffusion impedance inside the material. Reference Figures 1 to 3 , Figure 1 Schematic diagram of the cross-sectional structure of secondary particles in the positive electrode active material. Figure 2 This is a scanning electron microscope image of secondary particles in the positive electrode active material. Figure 3 This is a cross-sectional scanning electron microscope image of secondary particles in the positive electrode active material. Figures 1 to 3 It can be seen that the secondary particles have a hollow portion inside, that is, a hollow area inside, and are formed by cubic primary particles outside, with the long axis of the primary particles facing the hollow portion and arranged in a radial shape. It should be noted that the secondary particles include single-crystal-like or spherical agglomerates formed by the agglomeration of primary particles, wherein the primary particles (primary particles) refer to crystals that do not contain grain boundaries, and the crystallographic orientation of the crystals inside the primary particles is basically the same.
[0025] In some embodiments, the orientation distribution of the grains is tested by backscattered electron diffraction, the collection surface is a cross section through the center of the secondary particle, the normal direction of the collection surface is the Z-axis direction, and the secondary particles parallel to the Z-axis direction are <001> The crystal orientation ratio is N, which satisfies: 15%≤N≤60%. In some embodiments, N is 15%, 20%, 30%, 40%, 50%, 60% or any value therebetween. In some embodiments, 20%≤N≤50%. In some embodiments, 20%≤N≤45%. As a result, the secondary particles with a radial structure have a higher crystal orientation (crystal orientation ratio), which can expose more lithium ion transmission channels and achieve good electrolyte wettability, thereby achieving rapid extraction and embedding of lithium ions in the positive electrode material, improving the material rate performance and charge and discharge capabilities, thereby meeting the requirements of high energy density and fast charge and discharge, improving the cycle stability of the material under fast charging conditions, and extending the cycle life of the material. Reference Figure 4 The figure shows the reverse pole figure of the backscattered electron diffraction test of the secondary particles in the positive electrode active material. It can be seen from the figure that there are a large number of grains <001> The crystal orientation is parallel to the Z axis, that is, the high orientation strength is concentrated in <001> Crystal direction.
[0026] In some embodiments, the average diameter of the secondary particles is 6 μm to 16 μm. In some embodiments, the average diameter of the secondary particles is 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm or any value therebetween. In some embodiments, the average diameter of the secondary particles is 7.5 μm to 14 μm.
[0027] In some embodiments, the specific surface area of the secondary particles is 0.3 m 2 / g~1m 2 In some embodiments, the specific surface area of the secondary particles is 0.3 m 2 / g, 0.4m 2 / g, 0.5m 2 / g, 0.6m 2 / g, 0.7m 2 / g, 0.8m 2 / g, 0.9m 2 / g, 1m 2 In some embodiments, the specific surface area of the secondary particles is 0.4 m 2 / g~0.8m 2 / g.
[0028] In some embodiments, the average diameter of the hollow portion is 0.2 μm to 3 μm. In some embodiments, the average diameter of the hollow portion is 0.2 μm, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm or any value therebetween. In some embodiments, the average diameter of the hollow portion is 0.5 μm to 2 μm.
[0029] In some embodiments, the average aspect ratio of the primary particles in the secondary particles is 1.5 to 4 by backscattered electron diffraction test. In some embodiments, the average aspect ratio of the primary particles is 1.5, 2, 2.5, 3, 3.5, 4 or any value therebetween. In some embodiments, the average aspect ratio of the primary particles is 1.5 to 3. In some embodiments, the average aspect ratio of the primary particles is 1.6 to 2.2. As a result, the aspect ratio of the primary particles in the secondary particles is larger, which can expose more lithium ion transmission channels and achieve good electrolyte wettability, thereby achieving rapid extraction and embedding of lithium ions in the positive electrode material, improving the material rate performance and charge and discharge capabilities, thereby meeting the requirements of high energy density and rapid charge and discharge, improving the cycle stability of the material under fast charging conditions, and extending the cycle life of the material. In some embodiments, the average aspect ratio of the primary particles can be obtained by backscattered electron diffraction (EBSD) testing. For example, the collection surface is the central cross-section of the spherical secondary particles, and the fitting elliptical aspect ratio mode is used for test fitting to obtain the average aspect ratio. Reference Figure 5 , is the aspect ratio distribution diagram of primary particles in secondary particles obtained by EBSD test. From the figure, it can be calculated that the average aspect ratio of primary particles is 2.
[0030] In some embodiments, the center of the secondary particle is located in the hollow region where the hollow portion is located. In some embodiments, the center of the secondary particle coincides with the center of the hollow region where the hollow portion is located.
[0031] In some embodiments, the diffusion direction of lithium ions in the secondary particles intersects with the long axis direction of the primary particles in the secondary particles. In some embodiments, the diffusion direction of lithium ions in the secondary particles is perpendicular to the long axis direction of the primary particles in the secondary particles. Figure 1 ,The arrow shown in the figure is the direction of lithium ion diffusion, that is, the lithium ion channel is exposed on the long side.
[0032] In summary, the positive electrode active material of the present application has at least one of the following advantages: excellent material structure stability, fast charging performance, rate performance, cycle stability and calendar life.
[0033] 2. Preparation Method of Positive Electrode Active Material
[0034] The present application also provides a method for preparing a positive electrode active material. The positive electrode active material prepared by this method can be the positive electrode active material described above, so that this method can have all the characteristics and advantages of the positive electrode active material described above, which will not be repeated again.
[0035] In some embodiments, the preparation method includes: mixing metal oxide particles with an alkaline solution to form a first mixed solution; adding a metal salt mixed solution, a precipitant and a complexing agent to the first mixed solution, and sequentially performing a heating reaction treatment and an aging treatment to form a ternary precursor having a hollow structure inside, wherein the metal salt mixed solution includes Ni, Co and Mn elements; mixing the ternary precursor and a dopant, and performing a first calcination treatment to form a first product; mixing the first product and a first coating agent, and performing a second calcination treatment to form a second product; mixing the second product and a second coating agent, and performing a third calcination treatment to form the positive electrode active material.
[0036] In some embodiments, the positive electrode active material prepared by the method includes: secondary particles, the secondary particles are formed by aggregation of primary particles, the secondary particles have a hollow portion inside, the long axis direction of the primary particles in the secondary particles is toward the hollow portion, and the primary particles are arranged in a radial shape. The positive electrode active material prepared by the method can be the positive electrode active material described above, and thus, can have all the characteristics and advantages of the positive electrode active material described above, which will not be repeated again.
[0037] In some embodiments, the preparation method comprises:
[0038] S100: mixing metal oxide particles with an alkaline solution to form a first mixed solution;
[0039] In this step, the metal oxide particles are Al 2 O 3 , can be spherical or quasi-spherical, with an average particle size of 0.5 to 1.5 μm, specifically, the average particle size is 0.5 μm, 0.8 μm, 1 μm, 1.2 μm, 1.5 μm, and more specifically, the average particle size is 1 μm. In some embodiments, the alkaline solution includes NaOH solution and NH3 ·H 2 In some embodiments, the alkaline solution includes NaOH solution and NH 3 ·H 2 O solution, the concentration of NaOH solution is 3.5-4.5 mol / L, specifically 4 mol / L, NH 3 ·H 2 The concentration of the O solution is 0.1-0.2 mol / L, and may be specifically 0.12 mol / L. In some embodiments, the pH of the first mixed solution is controlled to be 10-12, and may be specifically 11.3.
[0040] S200: adding a metal salt mixed solution, a precipitant and a complexing agent to the first mixed solution, and sequentially performing a heating reaction treatment and an aging treatment to form a ternary precursor having a hollow structure inside; wherein the metal salt mixed solution includes Ni, Co and Mn elements.
[0041] In this step, the order of adding the metal salt mixed solution, the precipitant and the complexing agent is not particularly limited, and only needs to form the desired product. For example, the metal salt mixed solution, the precipitant and the complexing agent can be added in sequence. In this step, the metal salt mixed solution includes a nickel source, a cobalt source, a manganese source and deionized water. In this step, the specific types of the nickel source, the cobalt source and the manganese source are not particularly limited, and only need to form the desired product. For example, the nickel source, the cobalt source and the manganese source can be selected from the sulfates of Ni, Co and Mn, respectively. In some embodiments, in the metal salt mixed solution, the molar ratio of the nickel source, the cobalt source and the manganese source is (60-96): (1-20): (1-20), specifically, it can be (88-96): (1-10): (1-5), (90-96): (2-10): (2-5), more specifically, it can be 91:6:3. In some embodiments, the total molar concentration of the metal salt mixed solution is 2.5 to 3.5 mol / L, specifically 3 mol / L. In some embodiments, the nickel source may be nickel sulfate, the cobalt source may be cobalt sulfate, and the manganese source may be manganese sulfate. In some embodiments, the precipitant includes a NaOH solution, and the complexing agent includes NH 3 ·H 2 O solution.
[0042] In some embodiments, the temperature of the heating reaction is 30°C to 50°C, and the time is 10h to 14h. In some embodiments, the temperature of the heating reaction is 30°C, 32°C, 35°C, 38°C, 40°C, 42°C, 45°C, 48°C, 50°C or any value therebetween, and the time is 10h, 11h, 12h, 13h, 14h or any value therebetween. In some embodiments, the temperature of the heating reaction is 40°C, and the time is 12h. In some embodiments, the aging time is 4h to 8h, specifically 6h. In some embodiments, this step also includes post-treatment, for example, after aging, filtering, washing and drying to obtain a ternary precursor with a hollow portion inside.
[0043] The principle of the above-mentioned ternary precursor forming a hollow portion is as follows: the metal oxide particles (Al 2 O 3 After the spherical particles are mixed with the alkaline solution, the following reaction occurs first: Al 2 O 3 +2OH - →2Al(OH) 3 ; Subsequently, a metal salt mixed solution, a precipitant and a complexing agent are added, and a heating reaction treatment and an aging treatment are performed in sequence. During the heating reaction treatment, the products of the reaction of the metal elements Ni, Co and Mn in the metal salt will be in Al(OH) 3 Surface deposition, then, during aging, the following reaction occurs: Al(OH) 3 + excess NaOH → NaAlO 2 +2H 2 O, that is, using Al(OH) 3 It can react with NaOH to convert the Al(OH) 3 dissolves to form a hollow part. The overall reaction is Al 2 O 3 +2NaOH→2NaAlO 2 +H 2 O.
[0044] In some embodiments, the ternary precursor includes Ni s Co t Mn u (OH) 2 , 0.6≤s≤0.96, 0≤t≤0.2, 0≤u≤0.2, s+t+u=1. In some embodiments, s is 0.6, 0.7, 0.8, 0.9, 0.95, 0.96 or any value therebetween. In some embodiments, t is 0, 0.1, 0.15, 0.2 or any value therebetween, and u is 0, 0.1, 0.15, 0.2 or any value therebetween.
[0045] S300: mixing the ternary precursor and the dopant, and performing a first calcination process to form a first product;
[0046] In this step, the temperature of the first calcination treatment is 400°C to 800°C, and the time is 15h to 20h. In some embodiments, the first calcination treatment includes calcining at a first temperature for a first time, and then calcining at a second temperature for a second time. In some embodiments, the first temperature is 400°C to 600°C, the first time is 3h to 8h, the second temperature is 700°C to 800°C, and the second time is 10h to 15h. In some embodiments, the first temperature is 400°C, 450°C, 500°C, 550°C, 600°C or any value therebetween, the first time is 3h, 4h, 5h, 6h, 7h, 8h or any value therebetween, the second temperature is 700°C, 720°C, 740°C, 760°C, 780°C, 800°C or any value therebetween, and the second time is 10h, 11h, 12h, 13h, 14h, 15h or any value therebetween. In some embodiments, the first calcination treatment comprises calcination at 480° C. for 5 h, and then calcination at 750° C. for 12 h.
[0047] In some embodiments, the dopant includes at least one of carbonates, oxides, fluorides and hydroxides of Li, Mg, Sr, Ba, Al, Y, Zr, Ti, Si, Sn, V, B, P, W, and Mo. In some embodiments, the dopant includes WO 3 、ZrO 2 、Al 2 O 3 and LiOH·H 2 In some embodiments, the dopant includes WO 3 、ZrO 2 、Al 2 O 3 and LiOH·H 2 O. In some embodiments, the mass ratio of the ternary precursor to the dopant is 1:(0.8-1.1). In some embodiments, the mass ratio of the ternary precursor to the dopant is 1:(0.9-1).
[0048] S400: mixing the first product and the first coating agent, and performing a second calcination treatment to form a second product;
[0049] In this step, the temperature of the second calcination treatment is 600°C to 700°C, and the time is 10h to 14h. In some embodiments, the first product can be mechanically finely ground first, and then mixed with the first coating agent, and the second calcination treatment is performed under an oxygen gas atmosphere. In some embodiments, the temperature of the second calcination treatment is 600°C, 620°C, 640°C, 660°C, 680°C, 700°C or any value therebetween, and the time is 10h, 11h, 12h, 13h, 14h or any value therebetween.
[0050] In some embodiments, the first coating agent includes at least one of carbonates, oxides, fluorides and hydroxides of Mg, Sr, Ba, Al, Y, Zr, Ti, Si, Sn, V, B, P, W and Mo. In some embodiments, the first coating agent includes Co(OH) 2 and Al 2 O 3 In some embodiments, the first coating agent comprises Co(OH) 2 and Al 2 O 3 In some embodiments, based on the mass of the first product and the first coating agent, the mass percentage of the metal element in the first coating agent is 0.1% to 1%. In some embodiments, based on the mass of the first product and the first coating agent, the mass percentage of the metal element in the first coating agent is 0.5% to 0.9%.
[0051] S500: mixing the second product and the second coating agent, and performing a third calcination treatment to form the positive electrode active material.
[0052] In this step, the temperature of the third calcination treatment is 200°C to 400°C, and the time is 6h to 10h. In some embodiments, the temperature of the third calcination treatment is 200°C, 250°C, 300°C, 350°C, 400°C, or any value therebetween, and the time is 6h, 7h, 8h, 9h, 10h, or any value therebetween.
[0053] In some embodiments, the second coating agent includes at least one of carbonates, oxides, fluorides and hydroxides of Mg, Sr, Ba, Al, Y, Zr, Ti, Si, Sn, V, B, P, W and Mo. In some embodiments, the second coating agent includes H 3 BO 3 and Al 2 O 3 In some embodiments, the second coating agent comprises H 3 BO 3 and Al2 O 3 In some embodiments, the mass percentage of the metal element in the second coating agent is 0.05% to 0.5% based on the mass of the second product and the second coating agent. In some embodiments, the mass percentage of the metal element in the first coating agent is 0.1% to 0.3% based on the mass of the first product and the second coating agent.
[0054] In summary, the positive electrode active material prepared by the preparation method of the present application has at least one of the following advantages: excellent material structure stability, fast charging performance, rate performance, cycle stability and calendar life.
[0055] 3. Secondary battery
[0056] The present application also provides a secondary battery, which includes the positive electrode active material described above or the positive electrode active material formed by the preparation method described above. Thus, the device can have all the features and advantages of the positive electrode active material or preparation method described above, which will not be repeated here.
[0057] In some embodiments, the secondary battery includes a positive electrode sheet, a negative electrode sheet and an electrolyte. The positive electrode sheet includes a positive electrode collector and a positive electrode active material disposed on the positive electrode collector, and the positive electrode active material includes the positive electrode active material described above or the positive electrode active material formed by the preparation method described above.
[0058] In some embodiments, the positive electrode active material layer further includes a binder and a conductive material. The binder improves the bonding between the positive electrode active material particles and also improves the bonding between the positive electrode active material and the current collector. In some embodiments, the binder includes: polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene 1,1-difluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic (ester) styrene-butadiene rubber, epoxy resin or nylon, etc. In some embodiments, the conductive material includes: carbon-based materials, metal-based materials, conductive polymers and mixtures thereof. In some embodiments, the carbon-based material is selected from natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber or any combination thereof. In some embodiments, the metal-based material is selected from metal powder, metal fiber, copper, nickel, aluminum or silver. In some embodiments, the conductive polymer is a polyphenylene derivative.
[0059] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, silver alloy, etc.) on a polymer substrate.
[0060] In some embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material disposed on the negative electrode current collector, and the negative electrode active material includes at least one of a carbon-based material, a silicon-based material, a tin-based material, a phosphorus-based material, and metallic lithium. In some embodiments, the carbon-based material includes at least one of graphite, soft carbon, hard carbon, carbon nanotubes, and graphene, the silicon-based material includes at least one of silicon, silicon alloys, silicon oxides, and silicon carbon compounds, the tin-based material includes at least one of tin, tin oxides, and tin alloys, and the phosphorus-based material includes phosphorus and / or phosphorus-carbon composites. In some embodiments, the negative electrode active material includes a carbon-based material. In some embodiments, the negative electrode active material includes a carbon-based material and a silicon-based material, and the mass percentage content of the silicon-based material is 0% to 30% based on the mass of the negative electrode active material. Based on the mass of the negative electrode active material, the mass percentage content of the silicon-based material is 0%, 2%, 5%, 8%, 10%, 12%, 15%, 18%, 20%, 25%, 30%, or any value therebetween. Based on the mass of the negative electrode active material, the mass percentage content of the silicon-based material is 0% to 5%.Based on the mass of the negative electrode active material, the mass percentage content of the silicon-based material is 0% to 15%.
[0061] In some embodiments, the negative electrode active material layer further includes a binder and a conductive agent. In some embodiments, the binder includes: polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene 1,1-difluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic (ester) styrene-butadiene rubber, epoxy resin or nylon, etc. In some embodiments, the conductive agent includes: carbon-based materials, metal-based materials, conductive polymers and mixtures thereof. In some embodiments, the carbon-based material is selected from natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber or any combination thereof. In some embodiments, the metal-based material is selected from metal powder, metal fiber, copper, nickel, aluminum or silver. In some embodiments, the conductive polymer is a polyphenylene derivative.
[0062] In some embodiments, the negative electrode current collector includes: copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, or any combination thereof.
[0063] In some embodiments, the electrolyte includes a lithium salt, a solvent, and an additive.
[0064] In some embodiments, the lithium salt includes lithium hexafluorophosphate (LiPF 6 ), lithium tetrafluoroborate (LiBF 4), lithium trifluorosulfonyl (LiTf), lithium bis(fluorosulfonyl)imide (LiFSI), lithium trifluoromethanesulfonate, lithium (trifluoromethylsulfonyl)(perfluorobutylsulfonyl)imide (LiFNFSI), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium bis(pentafluoroethylsulfonyl)imide (LiBETI), lithium bis(fluoromalonate)borate (LiBFMB), lithium bis(oxalatoborate) (LiBOB), lithium difluorooxalatoborate (LiDFOB), lithium difluorobis(oxalatophosphate) and lithium 4,5-dicyano-2-(trifluoromethyl)imidazole (LiTDI).
[0065] In some embodiments, the mass percentage content of lithium salt is 4% to 25% based on the mass of the electrolyte. In some embodiments, the mass percentage content of lithium salt is 4%, 4.5%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25% or any value therebetween. In some embodiments, the mass percentage content of lithium salt is 6% to 18%.
[0066] In some embodiments, the solvent includes at least one of a linear carbonate and a cyclic carbonate.
[0067] In some embodiments, the linear carbonate is selected from at least one of dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, ethyl propyl carbonate and fluorinated linear carbonate. In some embodiments, the cyclic carbonate includes at least one of ethylene carbonate, propylene carbonate and butylene carbonate. In some embodiments, the organic solvent also includes non-fluorinated carboxylic acid esters, and the non-fluorinated carboxylic acid esters are selected from at least one of methyl formate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate and gamma-butyrolactone.
[0068] In some embodiments, the mass percentage content of the solvent is 40% to 80% based on the mass of the electrolyte. In some embodiments, the mass percentage content of the solvent is 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80% or any value therebetween. In some embodiments, the mass percentage content of the solvent is 50% to 70%.
[0069] In some embodiments, the additive includes at least one of a cyclic carbonate containing a carbon-carbon double bond, a silyl-containing phosphate and a nitrile compound salt. In some embodiments, the additive includes at least one of vinylene carbonate (VC), vinyl ethylene carbonate, tris(trimethylsilyl) phosphate (TMSP), tris(trimethylsilyl) borate (TMSB), succinonitrile, adiponitrile, glutaronitrile and hexanetrinitrile. In some embodiments, the additive further includes at least one of methylene methyl disulfonate (MMDS), ethylene ethyl disulfonate, 1,3-propane sultone (1,3-PS), 1-propylene-1,3-sultone (PST), 1,4-butane sultone (1,4-BS), diethylene sulfate (DTD), 4-methylethylene sulfate (PCS), 4-ethylethylene sulfate (PES), 4-propylethylene sulfate (PEGLST), propylene sulfate (TS), ethylene sulfite (DTO), dimethyl sulfite (DMS) and diethyl sulfite (DES).
[0070] In some embodiments, the mass percentage content of the additive is 0.05% to 10% based on the mass of the electrolyte. In some embodiments, the mass percentage content of the additive is 0.05%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 6%, 7%, 8%, 9%, 10% or any value therebetween. In some embodiments, the mass percentage content of the additive is 0.1% to 5%.
[0071] In some embodiments, a separator is provided between the positive electrode plate and the negative electrode plate to prevent short circuit. The material and shape of the separator that can be used in the embodiments of the present application are not particularly limited, and it can be any technology disclosed in the prior art. In some embodiments, the separator includes a polymer or an inorganic substance formed of a material that is stable to the electrolyte of the present application.
[0072] For example, the isolation film may include a substrate layer and a surface treatment layer. The substrate layer is a non-woven fabric, a film or a composite film having a porous structure, and the material of the substrate layer includes at least one of polyethylene, polypropylene, polyethylene terephthalate and polyimide. Specifically, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film can be selected.
[0073] A surface treatment layer is disposed on at least one surface of the substrate layer. The surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by mixing a polymer and an inorganic layer.
[0074] The inorganic layer includes inorganic particles and a binder, wherein the inorganic particles include at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide and barium sulfate. The binder includes at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride and hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene and polyhexafluoropropylene.
[0075] The polymer layer contains polymers, and the polymer material includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylic acid salt, polyvinylpyrrolidone, polyvinyl ether, polyvinylidene fluoride and poly(vinylidene fluoride-hexafluoropropylene).
[0076] In some embodiments, the method for preparing the secondary battery includes providing an electrode assembly, injecting liquid, packaging and forming. In some embodiments, the temperature of the forming is 40°C to 50°C, for example, 41°C, 42°C, 43°C, 44°C, 45°C, 46°C, 47°C, 48°C or 49°C.
[0077] In some embodiments, the formation includes: charging to 3.9V at 0.05C current and standing for 24h at a temperature of 40°C to 50°C, such as 45°C, and a pressure of 150kgf to 750kgf, such as 600kgf, followed by charging to 4.4V at 0.1C, and then discharging to 2.8V at 0.2C.
[0078] In some embodiments, the secondary battery is a lithium secondary battery or a sodium secondary battery. In some embodiments, the lithium secondary battery includes, but is not limited to: a lithium metal secondary battery, a lithium ion secondary battery, a lithium polymer secondary battery or a lithium ion polymer secondary battery.
[0079] In some embodiments, the secondary battery may include an outer package, which may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer package of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), polybutylene succinate (PBS), etc.
[0080] In some embodiments, the shape of the secondary battery is not particularly limited, and it can be cylindrical, square, or any other shape.
[0081] In some embodiments, the present application further provides a battery module. The battery module includes the above-mentioned secondary battery. The battery module of the present application uses the above-mentioned secondary battery, and therefore has at least the same advantages as the secondary battery. The number of secondary batteries contained in the battery module of the present application can be multiple, and the specific number can be adjusted according to the application and capacity of the battery module.
[0082] In some embodiments, the present application further provides a battery pack, which includes the above-mentioned battery module. The number of battery modules included in the battery pack can be adjusted according to the application and capacity of the battery pack.
[0083] 4. Device
[0084] The present application also provides a device, which includes at least one of the above-mentioned secondary battery, battery module and battery pack. Therefore, the device can have all the features and advantages of the above-mentioned secondary battery, battery module or battery pack, which will not be repeated here.
[0085] In some embodiments, the device includes, but is not limited to: electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, power storage systems, etc. In order to meet the device's requirements for high power and high energy density of secondary batteries, a battery pack or battery module may be used.
[0086] In other embodiments, the device may be a mobile phone, a tablet computer, a laptop computer, etc. The device is usually required to be light and thin, and a secondary battery may be used as a power source.
[0087] Examples and Comparative Examples
[0088] Example 1
[0089] Preparation of positive electrode active material precursor: Step (1), under an inert atmosphere, nickel sulfate, cobalt sulfate, and manganese sulfate are dissolved in deionized water to a total molar concentration of 3 mol / L, and the molar ratio of nickel element, cobalt element, and manganese element is 91:6:3 to obtain a metal salt mixed solution, and 4 mol / L NaOH solution, 2 mol / L NH 3 ·H 2 Step (2), prepare the base solution, add pure water, the ammonia water prepared in step 1, the NaOH solution and 400g of Al with a diameter of 1μm into the reactor under nitrogen atmosphere. 2 O 3 Spherical particles, the concentration of ammonia water is controlled to be 0.12 mol / L, and the pH is 11.3. Step (3), the metal salt mixed solution prepared in step 1, the precipitant NaOH solution and the complexing agent NH 3 ·H 2O solution, pH controlled at 11.0, reaction temperature controlled at 40°C, reaction time 40h. Step (4), transfer the reaction solution of step 3 to an aging kettle, adjust the pH to 13.5 with NaOH solution, aging time 6h. After filtration, washing and drying, the precursor powder Ni with a hollow interior is obtained. 0.91 Co 0.06 Mn 0.03 (OH) 2 .
[0090] Preparation of positive electrode active material: Step (1), Ni 0.91 Co 0.06 Mn 0.03 (OH) 2 Precursor, dopant WO 3 , dopant ZrO 2 、Dopant Al 2 O 3 and dopant LiOH·H 2 O are weighed and mixed according to a molar ratio of 0.98:0.01:0.005:0.005:1.02, placed in a crucible, calcined at 480°C for 5 hours in an oxygen atmosphere, and then calcined at 730°C for 12 hours, and cooled to room temperature. Step (2), after mechanical fine grinding, the obtained powder is coated with a coating agent Co(OH) 2 and coating agent Al 2 O 3 A high-speed dry mixing primary coating is performed, wherein the Co element accounts for 0.6% by weight of the powder material, and the Al element accounts for 0.1% by weight of the powder material. The temperature is raised to 650°C at a rate of 3°C / min, and the temperature is kept for 12 hours in an oxygen gas atmosphere. After cooling, a primary coated material is obtained. Step (3), the primary coated material is mixed with a coating agent boric acid (H 3 BO 3 ) and coating agent Al 2 O 3 High-speed dry mixing is performed, wherein the weight percentage of B element in the powder material is 0.08%, and the weight percentage of Al element in the powder material is 0.1%. The temperature is raised to 300°C at a rate of 3°C / min, and sintered three times for 8 hours in an oxygen atmosphere to obtain the final product, i.e., a positive electrode active material with a hollow portion inside.
[0091] The preparation steps of the positive electrode plate are as follows: the positive electrode active material with a hollow part inside, CNT (conductive agent carbon nanotube) / Super-P (conductive carbon black), and binder polyvinylidene fluoride PVDF obtained above are mixed in N-methylpyrrolidone NMP at a weight ratio of positive electrode active material: CNT / Super-P:PVDF=95:(1.0 / 2.0):2, and after being fully homogenized (the slurry viscosity is 5000cps~8000cps, the fineness is 6μm, and the solid content is 72%), it is coated on a 12μm thick aluminum current collector, and then the positive electrode plate is obtained through drying, rolling, hot pressing and other steps.
[0092] The preparation steps of the negative electrode plate are as follows: the negative electrode active material silicon oxide (SiOx, 0.5≤x≤1.5)-graphite composite (Si / C=5:95), the conductive agent acetylene black, the binder styrene butadiene rubber SBR, the thickener carboxymethyl cellulose CMC, and the polyacrylic acid PAA are added to deionized water in a weight ratio of 95:2:1.5:1:0.5, and after sufficient homogenization (the viscosity of the slurry is 5000cps~8000cps, the fineness is 20μm, and the solid content is 40%), it is coated on an 8μm thick copper current collector, and then the negative electrode plate is obtained through drying, rolling, hot pressing and other steps.
[0093] Preparation of electrolyte: In a glove box filled with argon (H 2 O<0.1ppm,O 2 <0.1ppm), the lithium salt LiPF 6 Fully dissolve in a mixed solution of EC / DEC / EMC (ethylene carbonate / diethyl carbonate / ethyl methyl carbonate) = 25 / 20 / 55 to prepare a 1 mol / L solution.
[0094] Separator: A 11μm thick PE (polyethylene) porous polymer separator is used.
[0095] Preparation of lithium-ion secondary battery: The prepared positive electrode sheet, separator, and negative electrode sheet are overlapped in order, with the separator being located between the positive electrode sheet and the negative electrode sheet to obtain a bare cell, and the bare cell is placed in a punched aluminum-plastic film soft package shell, and after being fully dried, the prepared electrolyte is injected, and the battery is placed at 45°C for 48h, and formed in a high-temperature fixture (the formation conditions are: temperature 45°C, pressure 600kgf, 0.05C current charging to 3.9V and standing for 24h, then 0.1C charging to 4.4V, and then 0.2C discharge to 2.8V, after secondary sealing, conventional capacity division is performed.
[0096] Embodiments 2 to 5
[0097] Examples 2 to 9 are implemented on the basis of Example 1 by adjusting the core single crystal material, the feeding type and feeding amount of the coating material corresponding to the first coating layer, the feeding type and feeding amount of the coating material corresponding to the second coating layer, etc. Specific adjustment measures and detailed data are shown in Table 1.
[0098] Comparative Example 1
[0099] The other steps in Comparative Example 1 are the same as those in Example 1, except that the preparation of the positive electrode active material precursor is different, as follows:
[0100] Preparation of positive electrode active material precursor: Step (1), under an inert atmosphere, nickel sulfate, cobalt sulfate, and manganese sulfate are dissolved in deionized water to a total molar concentration of 3 mol / L, and the molar ratio of nickel element, cobalt element, and manganese element is 91:6:3. At the same time, 4 mol / L NaOH solution, 2 mol / L NH 3 ·H 2 O solution. Step (2), prepare the base solution, add pure water, the ammonia solution prepared in step 1, and the NaOH solution into a reactor under a nitrogen atmosphere, and control the ammonia concentration to be 0.12 mol / L and the pH to be 11.5. Step (3) add the salt solution prepared in step 1, the precipitant NaOH solution, and the complexing agent NH 3 ·H 2 O solution, pH controlled at 11.5, reaction temperature controlled at 40°C, reaction time 20h. Step (4) Transfer the reaction solution of step 3 to an aging kettle, aging time 6h. After filtration, washing and drying, the precursor powder Ni without hollow structure is obtained. 0.91 Co 0.06 Mn 0.03 (OH) 2 .
[0101] Comparative Example 2
[0102] The other steps in Comparative Example 2 are the same as those in Example 1, except that the preparation steps of the positive electrode active material are different, as follows:
[0103] Preparation of positive electrode active material: Step (1), Ni 0.91 Co 0.06 Mn 0.03 (OH) 2 Precursor, dopant ZrO 2 and dopant LiOH·H 2O are weighed and mixed in a molar ratio of 0.98:0.02:1.02, placed in a crucible, calcined at 480°C for 5 h in an oxygen atmosphere, and then calcined at 780°C for 12 h, and cooled to room temperature. Step (2), after mechanical fine grinding, the obtained powder is coated with a coating agent Co(OH) 2 and coating agent Al 2 O 3 A high-speed dry mixing primary coating is performed, wherein the Co element accounts for 0.6% by weight of the powder material, and the Al element accounts for 0.1% by weight of the powder material. The temperature is raised to 650°C at a rate of 3°C / min, and the temperature is kept for 12 hours in an oxygen gas atmosphere. After cooling, a primary coated material is obtained. Step (3), the primary coated material is mixed with a coating agent boric acid (H 3 BO 3 ) and coating agent Al 2 O 3 High-speed dry mixing is performed, wherein the weight percentage of B element in the powder material is 0.08%, and the weight percentage of Al element in the powder material is 0.1%. The temperature is raised to 300°C at a rate of 3°C / min, and sintered three times for 8 hours in an oxygen atmosphere to obtain the final product, i.e., a positive electrode active material with a hollow portion inside.
[0104] Test Method
[0105] 1. Electron Backscatter Diffraction (EBSD) Test
[0106] The positive electrode sheet was cut into sections by ion milling (argon ion beam sputtering), and the sections were used as the collection surfaces. The samples were sent to the electron backscatter diffraction (EBSD) test equipment. The normal direction of the collection surface was set to the Z-axis direction. 4-6 spherical secondary particles were selected (the selection criteria were that the exposed sections were spherical and eccentric), and the BC+IPF+GB images parallel to the Z direction were collected. The data were processed as follows: 1) The "fit ellipse aspect ratio" mode was selected and the aspect ratio distribution analysis was performed, for example Figure 5 ; 2) Set the conditions to <001> The crystal direction is parallel to the Z axis, and the pixel area of this region is analyzed, and its proportion of the total identification area is calculated as the crystal direction ratio N, for example Figure 4 .
[0107] 2.25℃ cycle life test:
[0108] (1) The lithium-ion battery was allowed to stand at 25°C for 6 h; (2) the battery was discharged at 1C to 2.5 V; (3) after standing for 30 min, the battery was charged at 1C CC-CV to 4.25 V with a cut-off current of 0.05C; (4) after standing for 30 min, the battery was discharged at 1C to 2.5 V with a cut-off current of 0.05C; this capacity was taken as the initial capacity C0; (5) steps 3 to 4 were repeated until the discharge capacity decayed to 80% of C0, and the total number of cycles was recorded.
[0109] 3. 45℃ cycle life
[0110] The lithium-ion secondary battery was subjected to a cycle test at a constant temperature of 45°C (charged at 1C to 4.25V, then discharged at 1C to 2.8V, and so on) until the capacity retention rate decayed to 80%, and the total number of cycles was recorded.
[0111] 4. DCR (impedance) test
[0112] (1) The lithium-ion battery was allowed to stand at 25°C for 6 h; (2) the battery was discharged at 0.33C to 2.5 V; (3) after standing for 30 min, the battery was charged at 0.33CCC-CV to 4.25 V, with a cut-off current of 0.05C and a recorded capacity of C0; (4) after standing for 30 min, the battery was discharged at 0.33C to 50% of C0; (5) after standing for 30 min, the end voltage was recorded as V1, and a DCR test was performed using a 2C 10s pulse current (I), with the end voltage recorded as V2, DCR = (V2-V1) / I.
[0113] Test Results
[0114] Table 1
[0115]
[0116]
[0117] It can be seen from Examples 1 to 5 and Comparative Examples 1 to 2 that the positive active material of the present application includes secondary particles, which have a hollow radial (radiative) structure, which can well release the stress (intergranular stress) generated by the phase change of the ternary positive electrode material under high SOC, improve the structural stability of the material, have good mechanical properties, reduce the microcracks caused by stress, avoid the exposed fresh interface from reacting with the electrolyte, thereby achieving the improvement of the cyclic stability of the material. On the other hand, the radial structure of the secondary particles has a high crystal orientation (crystal orientation ratio), and the aspect ratio of the primary particles in the secondary particles is larger, which can expose more lithium ion transmission channels, achieve good electrolyte wettability, thereby achieving rapid release and embedding of lithium ions in the positive electrode material, improving the material rate performance and charge and discharge capacity, thereby meeting the requirements of high energy density and rapid charge and discharge, improving the cyclic stability of the material under fast charge conditions, and extending the cycle life of the material. In addition, the major axis direction of the primary particles in the secondary particles is toward the hollow part, and is arranged in a radial shape. The secondary particles arranged in the radial direction have high conductivity and excellent electrical conductivity, which further reduces the internal lithium ion diffusion impedance of the material.
[0118] By comparing Comparative Example 1 with Examples 1 to 5, it can be seen that the interior of the secondary particles in Comparative Example 1 does not have a hollow portion, and thus the material structure stability and mechanical properties are poor, microcracks will be generated under stress, and the exposed fresh interface will react with the electrolyte, the material cycle stability will deteriorate, and thus the cycle life will be significantly reduced and the impedance will increase.
[0119] Comparing Comparative Example 2 with Examples 1 to 5, it can be seen that although the secondary particles in Comparative Example 2 have a hollow portion inside, the EBSD test parallel to the Z axis direction <001> The crystal orientation ratio of the crystal direction is only 10%, which is far lower than 15%. Therefore, the crystal orientation degree (crystal orientation ratio) of the material is low, and the orientation is not close, which is not conducive to the rapid transmission of lithium ions, affecting the material's rate performance and charge and discharge capacity, and reducing the material's cycle stability and cycle life. In addition, the primary particles of the material have a low aspect ratio, which is not conducive to exposing more lithium ion transmission channels, poor electrolyte wettability, and increased impedance.
[0120] Although some exemplary embodiments of the present application have been illustrated and described, the present application is not limited to the disclosed embodiments. On the contrary, those skilled in the art will recognize that some modifications and changes may be made to the described embodiments without departing from the spirit and scope of the present application as described in the appended claims.
Claims
1. A positive electrode active material, characterized in that: The chemical formula of the positive electrode active material is Li x Ni y Co z M1 a M2 b O c A d , 0.95≤x≤1.05, 0.8≤y≤1, 0≤z≤0.2, 0≤a≤0.2, 0≤b≤0.1, y+z+a+b=1, 1≤c≤2, 0≤d≤2, c+d≤2, M1 includes at least one of Mn and Al, M2 includes at least one of Zr, Zn, Cu, Cr, Sr, Mo, Mg, Fe, Ta, V, Ti, Y, La and Nb, and A includes at least one of N, F, S and Cl; The positive electrode active material comprises: Secondary particles, wherein the secondary particles are formed by agglomerating primary particles, the secondary particles have a hollow portion inside, and the long axis direction of the primary particles in the secondary particles faces the hollow portion and are arranged in a radial shape; Wherein, the orientation distribution of the grains is tested by backscattered electron diffraction, the collection surface is a cross section through the center of the secondary particle, the normal direction of the collection surface is the Z-axis direction, and the secondary particles parallel to the Z-axis direction are <001> The crystal orientation ratio of the crystal orientation is N, which satisfies: 15%≤N≤60%.
2. The positive electrode active material according to claim 1, characterized in that At least a portion of the primary particles in the secondary particles are arranged radially along a radial direction from the center of the secondary particles toward the surface; and / or The secondary particles are spherical or quasi-spherical; and / or 20%≤N≤50%。 3. The positive electrode active material according to claim 1, characterized in that The average diameter of the secondary particles is 6.0 μm to 16 μm; and / or The specific surface area of the secondary particles is 0.3 m 2 / g~1m 2 / g; and / or The average diameter of the hollow portion is 0.2 μm to 3 μm; and / or According to backscattered electron diffraction testing, the average aspect ratio of the primary particles in the secondary particles is 1.5-4.
4. The positive electrode active material according to claim 3, characterized in that The average diameter of the secondary particles is 7.5 μm to 14 μm; and / or The specific surface area of the secondary particles is 0.4 m 2 / g~0.8m 2 / g; and / or The average diameter of the hollow part is 0.5 μm to 2 μm; and / or According to backscattered electron diffraction testing, the average aspect ratio of the primary particles in the secondary particles is 1.5-3.
5. The positive electrode active material according to claim 1, characterized in that The center of the secondary particle is located in the hollow area where the hollow part is located; and / or The diffusion direction of lithium ions in the secondary particles intersects with the long axis direction of the primary particles in the secondary particles.
6. The positive electrode active material according to claim 5, characterized in that The center of the secondary particle coincides with the center of the hollow region where the hollow portion is located; and / or The diffusion direction of lithium ions in the secondary particles is perpendicular to the long axis direction of the primary particles in the secondary particles.
7. A method for preparing a positive electrode active material, characterized in that: include: mixing metal oxide particles with an alkaline solution to form a first mixed solution; Adding a metal salt mixed solution, a precipitant and a complexing agent to the first mixed solution, and sequentially performing a heating reaction treatment and an aging treatment to form a ternary precursor having a hollow structure inside; wherein the metal salt mixed solution includes Ni, Co and Mn elements; The ternary precursor and the dopant are mixed and subjected to a first calcination process to form a first product; The first product and the first coating agent are mixed and subjected to a second calcination treatment to form a second product; The second product and the second coating agent are mixed and subjected to a third calcination treatment to form the positive electrode active material; wherein the positive electrode active material includes: secondary particles, the secondary particles are formed by aggregation of primary particles, the interior of the secondary particles has a hollow portion, the long axis direction of the primary particles in the secondary particles is toward the hollow portion, and the particles are arranged in a radial shape.
8. The preparation method according to claim 7, characterized in that: The metal oxide particles are Al2O3, and the average particle size is 0.5 to 1.5 μm; and / or The alkaline solution comprises at least one of a NaOH solution and an NH3·H2O solution; and / or The metal salt mixed solution comprises a nickel source, a cobalt source, a manganese source and deionized water; and / or The precipitant comprises a NaOH solution; and / or The complexing agent comprises NH3·H2O solution; and / or The heating reaction temperature is 30°C to 50°C and the time is 10h to 14h; and / or The aging treatment time is 4h to 8h; and / or The temperature of the first calcination treatment is 400° C. to 800° C., and the time is 15 h to 20 h; and / or The temperature of the second calcination treatment is 600° C. to 700° C., and the time is 10 h to 14 h; and / or The temperature of the third calcination treatment is 200°C to 400°C and the time is 6h to 10h; and / or The ternary precursor includes Ni s Co t Mn u (OH)2, 0.6≤s≤0.96, 0≤t≤0.2, 0≤u≤0.2, s+t+u=1; and / or The dopant comprises at least one of carbonates, oxides, fluorides and hydroxides of Li, Mg, Sr, Ba, Al, Y, Zr, Ti, Si, Sn, V, B, P, W and Mo; and / or The first coating agent and the second coating agent respectively include at least one of carbonates, oxides, fluorides and hydroxides of Mg, Sr, Ba, Al, Y, Zr, Ti, Si, Sn, V, B, P, W and Mo.
9. A secondary battery, characterized in that: The invention comprises the positive electrode active material according to any one of claims 1 to 6 or the positive electrode active material formed by the preparation method according to any one of claims 7 to 8.
10. A device, characterized in that: A secondary battery comprising the secondary battery according to claim 9.